Traditional Chinese music as cultural heritage tourism in Malaysia - Chiu, M.Y. (2017)
This study intends to discuss the sustainability of Malaysian Chinese music and its furtherance in the perspective of tourism. Chinese are the majority of immigrants who have settled and resided in Malaysia for a long history. They brought in abundant cultures including music, which has genres such as Hua Yue Tuan (Chinese orchestra), 24 festive drums, Cantonese and Hokkien operas, Nanyin (southern music), Teochew music and so forth. However, it is worrisome that the society is much more westernised nowadays, and it causes the lack of appreciation and interest towards traditional Chinese music, as well as the loss of skilled performers, the amateurs, and the audience amongst younger generations. Since Malaysian government is currently making the tourism industry a main contributor to the socio-economic development, promoting traditional Chinese music in the perspective of tourism could be a positive way of reviving. Also, promoting the traditional Chinese music complies with one of Tourism Malaysia’s objectives—to showcase Malaysia’s unique cultures. The aim of this study is to firstly investigate the development of traditional Chinese music in Malaysia in term of diverse music genres; secondly, to realise the relationship between the diverse genres of traditional Chinese music and the locations/origins where these music genres have grown and developed; lastly, to study the relationship between these locations and the tourism, and see whether the design of the tourism could combine the tourist attractions with the appreciation of traditional Chinese music. Knowing the fact and issue that currently traditional Chinese music is facing will be helpful for sustaining this precious cultural treasure in Malaysia. It is hoped that through this study, the researchers, the music educators, and music performers will find efficient ways to enhance the promotion and popularization of traditional Chinese music in the perspective of tourism.